Pengaruh Status Refraksi terhadap Stereopsis Dekat pada Anak Usia Sekolah: Hasil Penelitian - Wahyudi, I Nyoman Surya Ari; Wulandari, Lely Retno; Anandita, Nanda Wahyu; Sulistiyowati, Anny (Cermin Dunia Kedokteran, 2025)
Introduction: This study aims to evaluate the effect of refractive status on near stereopsis function among school-age children. Methods: A population-based cross-sectional study in 13 orphanages in Malang city with 334 respondents. Visual acuity (VA) and inter-eye line difference were measured using LogMAR of LVRC chart. Refractive status was determined using spherical equivalent (SE) of autorefractometer, classified into emmetropia, myopia and hypermetropia (low, moderate, and high). Near stereopsis was measured using TNO and Butterfly test in arcsecond and completion time also calculated. Data were analyzed using Kruskal-Wallis and Spearman test. Results: There were significant differences of refractive status and inter-eye line difference to both TNO and butterfly score and time (p<0.05). The group with more severe refractive status and more inter-eye line difference in VA have lower stereopsis score and longer completion time. There were no differences between the age group to both TNO and butterfly score and time (p>0.05). There was a positive correlation between TNO and butterfly test (p<0.05, r= 0.365). Conclusion: There is a significant difference of refractive status and inter-eye line difference on near stereopsis function in school-aged children. Stereopsis test may be beneficial for screening of refractive disorder.